2022
DOI: 10.1039/d2cp02494b
|View full text |Cite
|
Sign up to set email alerts
|

Strong-field ionization of CH3Cl: proton migration and association

Abstract: Strong-field ionization of CH3Cl using femtosecond laser pulses, and the subsequent two-body dissociation of CH3Cl2+ along Hn+ (n =1-3) and HCl+ forming pathways, have been experimentally studied in a home-built...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 83 publications
2
8
0
Order By: Relevance
“…A relatively large variation in the energy of three levels indicates that the transition states involving the H−Cl and C−Cl bonds dissociation are sensitive to the description of the electron correlation. The reactions passing through the transition states, TS5 Cl and TS6 Cl , occur as experimentally reported 7,8,26 for the generation of CH 2 + + HCl + because the energies of TS5 Cl and TS6 Cl are lower than the 44.1 kcal/mol of the starting ionized state, 1 Cl . In the molecular dynamics simulations, there were three and one trajectories when the reactions occurred through TS5 Cl and TS6 Cl , respectively.…”
Section: Ts8mentioning
confidence: 64%
See 4 more Smart Citations
“…A relatively large variation in the energy of three levels indicates that the transition states involving the H−Cl and C−Cl bonds dissociation are sensitive to the description of the electron correlation. The reactions passing through the transition states, TS5 Cl and TS6 Cl , occur as experimentally reported 7,8,26 for the generation of CH 2 + + HCl + because the energies of TS5 Cl and TS6 Cl are lower than the 44.1 kcal/mol of the starting ionized state, 1 Cl . In the molecular dynamics simulations, there were three and one trajectories when the reactions occurred through TS5 Cl and TS6 Cl , respectively.…”
Section: Ts8mentioning
confidence: 64%
“…The ionization-induced fragmentation of methyl halides is of great interest, because the methyl chloride is present in the stratosphere and interstellar medium and contributes to ozone depletion in the stratosphere. For this reason, numerous experimental and theoretical studies have been intensively conducted, with particular emphasis on the two important processes: (i) ionization and (ii) subsequent fragmentation reaction, ,, which together constitute the ionization-induced fragmentation reaction. Many experiments have shown that the doubly ionized methyl chloride yields not only H + and H 2 + but also H 3 + as well as other substances such as HCl + and Cl + .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations